PARENTING IN THE DIGITAL ERA: INDONESIAN PARENTS' ADAPTATION TO TECHNOLOGY - Wiyun Philipus Tangkin; Puji Yanti Fauziah; Bertha Natalina Silitonga (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Technological advancements in the digital era have significantly transformed human civilization, particularly in the way families interact and practice parenting. In Indonesia, these changes have become increasingly complex due to the growing access children have to the internet and digital devices from an early age. This phenomenon presents new challenges for parents, such as exposure to negative content, gadget addiction, reduced social interaction, and a digital literacy gap between parents and children. This study aims to explore in depth the dynamics of parenting in the digital era within the Indonesian context. The research employs a descriptive-qualitative approach, referring to various relevant national and international literature sources. Findings indicate that many parents still face confusion in setting boundaries and supervising their children’s digital activities, while others have begun to adopt more adaptive and digitally literate parenting approaches. This article also proposes several strategies that parents can implement, such as strengthening family communication, utilizing digital monitoring tools, and continuously enhancing their technological knowledge. With proper understanding and approach, parents in Indonesia can become effective partners in guiding their children to navigate the digital age safely, healthily, and with dignity.